Guinness : - Yenne, Bill (John Wiley & Sons, 2007)
Guinness Stout has a unique place in global beverage folklore. It's a beer with a long and colourful history and mythology that maintains a passionate following among beer connoisseurs around the world. Indeed, two billion pints are poured and enjoyed around the world each year.